Human Peripheral Blood Eosinophils Express High Levels of the Purinergic Receptor P2X4 - Paalme, Viiu; Rump, Airi; Mädo, Kati; Teras, Marina; Truumees, Birgit; Aitai, Helen; Ratas, Kristel; Bourge, Mickael; Chiang, Chi-Shiun; Ghalali, Aram; Tordjmann, Thierry; Teras, Jüri; et al. (Frontiers in Immunology, 2019)
Extracellular nucleotides are important mediators of cell activation and trigger multiple responses via membrane receptors known as purinergic receptors (P2). P2X receptors are ligand-gated ion channels, activated by extracellular ATP. P2X4 is one of the most sensitive purinergic receptors, that is typically expressed by neurons, microglia, and some epithelial and endothelial cells. P2X4 mediates neuropathic pain via brain-derived neurotrophic factor and is also involved in inflammation in response to high ATP release. It is therefore involved in multiple inflammatory pathologies as well as neurodegenerative diseases. We have produced monoclonal antibodies (mAb) directed against this important human P2X4 receptor. Focusing on two mAbs, we showed that they also recognize mouse and rat P2X4. We demonstrated that these mAbs can be used in flow cytometry, immunoprecipitation and immunohistochemistry, but not in Western blot assays, indicating that they target conformational epitopes. We also characterised the expression of P2X4 receptor on mouse and human peripheral blood lymphocytes (PBL). We showed that P2X4 is expressed at the surface of several leukocyte cell types, with the highest expression level on eosinophils, making them potentially sensitive to adenosine triphosphate (ATP). P2X4 is expressed by leucocytes, in human and mouse, with a significant gender difference, males having higher surface expression levels than females. Our findings reveal that PBL express significant levels of P2X4 receptor, and suggest an important role of this receptor in leukocyte activation by ATP, particularly in P2X4high expressing eosinophils.